REKAYASA PERANGKAT LUNAK SISTEM MANAJEMEN KONTEN MENGGUNAKAN FRAMEWORK CODEIGNITER - Immanuel Pandiangan; Nanan Rohman (STMIK Mardira Indonesia, Bandung, 2015)
The usage of websites today are not only used by professionals or business, usage of the website is now widely used by the community, small or large scale organizations, or individuals. Directly proportional to the number of web site usage in the community, creating websites are increase in great demand by the public, but the creating a website is still a problem when it should be faced with the need for a professional website builder or often called a webmaster, although constraints in the manufacturing site web can be overcome by the presence of the webmaster, but the cost in the supply of webmasters to create, manage and maintain a website is still fairly high, until founded a web site creation technology using software content management system that allows for individuals to create, manage and maintain a website with ease on their own. Content management systems simplify the creation of a website by providing a backend that is easily to understood by the people who have no knowledge in web programming. In the presence content management system is very diverse, but for content management systems in the country is still very small and still requires some knowledge of web programming, so the authors try to apply a content management system that minimizes the use of programming knowledge base website with codeigniter framework as one of the most widely documented framework so that many people who are able to create, manage and maintain web sites independently without the need to have knowledge of website programming. Keywords : Content management system, Web, Framework, Codeigniter, Webmaster